Post-reform trends in wage inequality: The case of urban Bolivia - Julius Spatz; Susan Steiner (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2002)
This paper seeks to contribute to the ongoing controversy on the distributional effects of structural reforms in developing countries. Applying inequality indices and Fields' (2001) decomposition methodology to Bolivian household survey data of the years 1989 to 1997, we identify recent trends in wage inequality of urban Bolivia. Using a rent-based dual-economy model, we can link these trends to the structural reforms undertaken in Bolivia since 1985.
Keywords: D31; J50; L16; O17; 330; Structural Reforms; Inequality; Dual Economy; Bolivia; Anpassungsprogramm des IWF; Wirtschaftsreform; Wirkungsanalyse; Einkommensverteilung; Städtische Armut; Dualökonomie; Lohnstruktur; Rent Seeking; Schätzung; Dekompositionsverfahren; Theorie; Bolivien